Развитие этмоидного отдела хрящевого черепа в эмбриогенезе ужа обыкновенного, Natrix natrix (Ophidia, Colubridae) - Шевердюкова, А.В. (Вестник зоологии, 2012)
Описано развитие этмоидного отдела хрящевого черепа Natrix natrix Linnaeus, 1758 на разных стадиях эмбриогенеза. Впервые для змей описана независимая от париетотектального хряща закладка planum antorbitale и ее самостоятельный очаг охрящевения, а также установлено наличие processus maxillaris anterior. Гипохоанальный хрящ формируется как независимая структура. The development of the ethmoidal region of Natrix natrix`s Linnaeus, 1758 chondrocranium at different stages of development is described. For the first time an independent appearance of the planum antorbitale and its independent centre of chondrification are described in snakes. Also for the first time for snakes the presence of processus maxillaris anterior was revealed. The hypochoanal cartilage is shown to develop as an independent structure.